The deadly route to collapse and the uncertain fate of Brazilian rupestrian grasslands - Fernandes, G. Wilson; Barbosa, N. P.U.; Alberton, B. [UNESP]; Barbieri, A.; Dirzo, R.; Goulart, F.; Guerra, T. J.; Morellato, L. P.C. [UNESP]; Solar, R. R.C. (Springer Nature, 2018)
Rupestrian grasslands are biodiverse, evolutionary old vegetation complexes that harbor more than 5000 species of vascular plants and one of the highest levels of plant endemism in the world. Growing on nutrient–impoverished soils and under harsh environmental conditions, these mountaintop ecosystems were once spared from major human interventions of agriculture and intensive cattle ranching. However, in Brazil, rupestrian grasslands have experienced one of the most extreme land use changes among all Brazilian ecosystems, suffering from ill policies leading to intense mining activities, uncontrolled tourism, and unplanned road construction. Indeed, the discovery of large mineral reserves, the adoption of ineffective conservation policies, and, going forward, climate change, are threatening this hyper-diverse ecosystem. Here, we shed light on the severe threats imposed by land-use changes in this ecosystem, modeling its future distribution under different scenarios. We uncover a catastrophic forecast that, if not halted, will lead to the loss of 82% of this unique ecosystem in the future, impacting ecosystem services at regional scales, including water and food security potentially affecting more than 50 million persons.
Keywords: Biodiversity; Campo rupestre; Cerrado; Espinhaço mountains; Mining; Sustainability